2021
DOI: 10.1002/nla.2423
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and efficient computations with Wronskian matrices of Bernstein and related bases

Abstract: In this article, we provide a bidiagonal decomposition of the Wronskian matrices of Bernstein bases of polynomials and other related bases such as the Bernstein basis of negative degree or the negative binomial basis. The mentioned bidiagonal decompositions are used to achieve algebraic computations with high relative accuracy for these Wronskian matrices. The numerical experiments illustrate the accuracy obtained using the proposed decomposition when computing inverse matrices, eigenvalues or singular values,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…On the other hand, although Wronskian and Gram matrices are very different, interestingly several applications of these matrices are presented together in [57]. The use of the bidiagonal decomposition to achieve accurate computations with different classes of totally positive Wronskian and Gram matrices has been presented, for instance, in [55,[58][59][60].…”
Section: Recent Extensionsmentioning
confidence: 99%
“…On the other hand, although Wronskian and Gram matrices are very different, interestingly several applications of these matrices are presented together in [57]. The use of the bidiagonal decomposition to achieve accurate computations with different classes of totally positive Wronskian and Gram matrices has been presented, for instance, in [55,[58][59][60].…”
Section: Recent Extensionsmentioning
confidence: 99%
“…where p i,i are the diagonal pivots of the Neville elimination of A, m i,j are the multipliers of the Neville elimination of A and mi,j are the multipliers of the Neville elimination of A T . Looking at the code of Algorithm 1 (which computes the entries of M given in formulas ( 13), (14), and ( 15) in an adequate way), we can assert that it preserves HRA because it satisfies the NIC condition. Its computational cost is of O(n 2 ) arithmetic operations, and it must be observed that the Lagrange-Vandermonde matrix A is not constructed, what implies an additional saving in storage space.…”
Section: Algorithm For the Bidiagonal Decompositionmentioning
confidence: 99%
“…differing) signs, and otherwise only adds or subtracts input data. Some classes of totally positive matrices for which there are fast and accurate algorithms for computing their bidiagonal decompositions (A) are, for instance, Cauchy-Vandermonde, 8 generalized Vandermonde, 9 Bernstein-Vandermonde, 10 Lupaş, 11 generalized Pascal matrices, 12 collocation matrices of the Lupaş-type (p,q)-analogue of the Bernstein basis, 13 Wronskian matrices, 14 or Gram matrices of Bernstein bases. 15 The Lagrange basis of the space Π n (t) of the polynomials of degree less than or equal to n, widely used in polynomial interpolation, is…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation